Malay Kinship Terms and Their Relationship to the Formation of Social Identity in West Kalimantan, Indonesia - Yusriadi, Yusriadi; Andrian, Bob; Hakim, Muhammad Lutfi; Asfar, Dedy Ari; Shin, Chong (Masyarakat Linguistik Indonesia Universitas Andalas, 2026)
This study examines Malay kinship terms and its role in shaping social identity among communities in West Kalimantan, Indonesia. Employing an ethnographic approach within the framework of Social Identity Theory, it analyzes how this terminology functions in everyday life. Data were collected through interviews with 33 Malay participants from nine regions of West Kalimantan, complemented by an analysis of published materials on local kinship. The results indicate that Malay kinship terms act as tools for social categorization, in-group identification, and social comparison across different ethnic communities, reflecting complex socio-historical processes and inter-ethnic relationships. The study also demonstrates the influence of the national language, which serves as both a lingua franca and a prestigious linguistic resource in this context. These findings contribute to ethnolinguistic theory by confirming that kinship terms constitute a reflexive social practice that shapes communal life in both literal and symbolic dimensions. Keywords: kinship terms; social identity; ethnolinguistics; Malay; West Kalimantan; Social identity theory